(Un)Fixing Aloula: Maps, images and paradigms of The Attic (Marble) Landscape - French, Chris; Mitsoula, Maria (Interstices: Journal of Architecture and Related Arts, 2022)
“(Un)fixing Aloula” explores the fragmented landscape of the Open-Air Museum of Quarry Arts in Aloula, Athens. This museum—located in disused marble quarries on Mount Pentelicon and “repaired” by sculptor Nella Golanda and architect Aspasia Kouzoupi—is presented as a “repair-scape”, in which marble remnants were laboriously transformed into a reimagined ground. The “fixing” of this site—the curation of unorganised waste matter into organised material—generated a landscape that is at once restored and yet ruined, a “reciprocal landscape” (following Hutton) in dialogue with Athens and the Attic basin. Through a narration of an encounter with the museum, of a conversation with Golanda and Kouzoupi, and of an imaging of the museum for an exhibition at the Fondation Hellénique, this paper offers a developed reading of the repair-scape as a site of sympoiēsis, and as a site in which our shared image of a city might be continually contested, unfixed.